2006
DOI: 10.1097/01.prs.0000220464.91795.07
|View full text |Cite
|
Sign up to set email alerts
|

Laserbrasion: The Combination of Carbon Dioxide Laser and Dermasanding

Abstract: Laserbrasion is an effective and safe method of reducing deep perioral wrinkles. The technique is easy to perform and inexpensive for the laser surgeon. Laserbrasion can yield better results than the laser alone and has the added benefit of a shorter healing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although there is currently no standard of care for laser resurfacing wounds, several reports have cited AHO as part of their postoperative regimen for keeping the wound site moist for both open and closed wound care protocols. 19,20,[27][28][29][30] In a survey of members of the American Academy of Facial Plastic and Reconstructive Surgery, AHO was the most frequently used (60%) postoperative dressing for facial resurfacing procedures, followed by petrolatum (34%). 31 Study subjects reported less stinging, itching, and tightness with AHO compared with BTE.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is currently no standard of care for laser resurfacing wounds, several reports have cited AHO as part of their postoperative regimen for keeping the wound site moist for both open and closed wound care protocols. 19,20,[27][28][29][30] In a survey of members of the American Academy of Facial Plastic and Reconstructive Surgery, AHO was the most frequently used (60%) postoperative dressing for facial resurfacing procedures, followed by petrolatum (34%). 31 Study subjects reported less stinging, itching, and tightness with AHO compared with BTE.…”
Section: Discussionmentioning
confidence: 99%
“…During the procedure, they must be kept in contact with the skin with a gentle pressure [225]. One of the alternative equipments that is useful for derm-abrasion of the scars is sterile, medium grade (220 grit) silicone carbide sandpaper that is wrapped around gauze [227].…”
Section: Dermabraders and Devicesmentioning
confidence: 99%